PENGARUH PERSEPSI KENYAMANAN DALAM PENGGUNAAN DIGITAL PAYMENT TERHADAP PERILAKU KONSUMTIF MASYARAKAT DI ERA INDUSTRI 4.0 DENGAN PERSEPSI KECEPATAN SEBAGAI VARIABEL MODERATING - Annisa Fauzia (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to examine the effect of perceived convenience in the use of digital payment on consumptive behavior in the industrial era 4.0 with perceived speed as a moderating variable. The sample used in this study is the digital payment user community in the Province of Yogyakarta Special Region. The sample study used convenience sampling method and obtained 91 respondents. This research uses SmartPLS 3.3.3 software. The results show that the perceived convenience of using digital payments has no effect on people's consumptive behavior in the industrial era 4.0 and the perception of speed cannot strengthen the influence of perceived convenience in using digital payments on people's consumptive behavior in the industrial era 4.0.